2016
DOI: 10.2175/106143015x14338845155787
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Design of a Clay‐Zeolite Medium for the Adsorption of Total Phosphorus from Wastewater

Abstract: Phosphorus significantly influences the eutrophication process, modifying the quality of waterways and habitat, especially in stagnant waterbodies exposed to septic tank effluent at high nutrient levels. This research explores the development of a cost-effective, efficient, and affordable on-site wastewater treatment system targeted as total phosphorus (TP) removal technology. The research objective is to demonstrate the TP removal efficiency of an optimized clay-zeolite medium by chemical adsorption. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The zeolite, bentonite, and kaolin powder mix were made into a paste with distilled water and then kneaded and passed through a manual extruder to form pellets 5 ± 0.1 mm long x 2 mm diameter. These were dried and calcined following Ciosek et al (Ciosek, Luk, Warner, and Warner, 2016). The pellets were oven-dried at 105 °C for 18 hours and then calcined at 600 °C for 6 hours, increasing the temperature at 5 °C/min.…”
Section: Pelletizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The zeolite, bentonite, and kaolin powder mix were made into a paste with distilled water and then kneaded and passed through a manual extruder to form pellets 5 ± 0.1 mm long x 2 mm diameter. These were dried and calcined following Ciosek et al (Ciosek, Luk, Warner, and Warner, 2016). The pellets were oven-dried at 105 °C for 18 hours and then calcined at 600 °C for 6 hours, increasing the temperature at 5 °C/min.…”
Section: Pelletizationmentioning
confidence: 99%
“…These were dried and calcined following recommendations by Ciosek et al (2016). The pellets were oven-dried at 105 °C for 18 hours and then calcined at 600 °C for 6 hours, increasing the temperature at 5 °C/min.…”
Section: Adsorption Columnmentioning
confidence: 99%
“…The wet granulation process is commonly used for manufacturing binder-containing zeolite with the addition of water in order to adjust the viscosity and plasticity of the mixture [25,26]. Several studies have demonstrated the use of clays as an inorganic binder in zeolite pellets [27][28][29][30][31][32][33]. The type and amount of the binder can affect the mechanical durability of the granulate and also the sorption capacity of the granulated material.…”
Section: Introductionmentioning
confidence: 99%